Penerapan Pembelajaran Berbasis Komik untuk Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam Siswa Sekolah Dasar - Wisudawati, Rina; Puspitasari, Yulia Dewi; Pratama, Hendrik (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The purpose of this study was to improve the learning outcomes of fourth grade students at SDN Banjardowo in the subject of Natural Sciences using comics media. Based on the initial test, the learning outcomes of fourth grade students who are taking science subjects at SDN Banjadowo Lengkong are in the unsatisfactory category. This type of research uses Classroom Action Assessment which is carried out in three cycles. The number of samples was 18 students with the subject Caring for Living Creatures and it was carried out in the even semester of 2021/2022. This study uses descriptive quantitative data analysis techniques obtained from the overall average presentation. The research shows that the learning outcomes of fourth grade students at SDN Banjardowo are 87.5%, the second cycle is 92.5%, and the third cycle is 97.5%. The results showed that the learning outcomes of fourth graders at SDN Banjardowo increased in the third cycle, by 5% from cycle I to cycle II and 5% from cycle II to cycle III. The conclusion in this study is that science comics learning media is very effective in helping to improve the learning outcomes of fourth grade students at SDN Banjardowo.